AlfaDatizando: a Data Visualization Platform to work Computational Thinking in Digital Humanities - Lliteras, Alejandra Beatriz (2022)
Computational Thinking is one of the fundamental skills of the 21st century and will be a necessary part of all future work, so it is essential that children learn it in school. One way to work on Computational Thinking is through data visualization. This paper presents the motivation, design and implementation of a platform called AlfaDatizando, through which it is possible to work with data visualization activities to promote the skill of Computational Thinking in Digital Humanities. AlfaDatizando allows the creation, resolution, and feedback of data visualization activities without the need to use another platform. It also allows sharing didactic sequences and data sources with the educational community registered in the platform. AlfaDatizando is still in an early stage of development.